Rancang Bangun Sistem Informasi Posyandu Stunting di Kabupaten Cilacap - zulfikar Yusya; Susanti; Fajar Nurwibowo (Himpunan Penggiat Teknologi Informasi Abrar Indonesia, 2022)
In this era of globalization, the need for computers in various aspects, especially in the field of health services, is very much needed. This need is part of the functionality in supporting public health services. Posyandu as a public health service, contributes to the welfare of the health of mothers and babies. But in reality they still use conventional methods in data processing. The Posyandu Information System (SINDU) performs data processing including basic Posyandu data regarding stunting, Posyandu service activities, starting from the process of weighing and checking the condition of babies and giving immunizations, Posyandu user data and Posyandu officers/cadres. processing toddler data and reports starting from entering, changing, updating, deleting and calculating the ideal weight of babies, toddlers, and mothers. Initially the Posyandu Information System was done manually by filling in the form provided by the Public Health Center, it needed to be developed into a computerized system. In this case, it can help health workers / Posyandu cadres in health services which include all kinds of Posyandu administration.